Manajemen Pendidikan Anak dalam Meningkatkan Perilaku dan Akhlak (Studi Lapangan di SMP Negeri Pakis Kabupaten Malang) - Wahyudi Widodo (Departement of Mathematics Education, 2024)
A godly child is one who devotes himself to one's parents and an ungodly son is a disobedient child to one's parents. Parental guidance and direction until it becomes successful if it is done well. So it is important for parents and schools to know the importance of children's education management. The research method used is qualitative with a descriptive type. The results show that 1) The education of children at SMPN cannot be separated from the education of parents. Where schools become a second home for children to learn, but the main role of parents is important. Many children or students have good morals and religious or other achievements caused by parents, especially maternal education, so it is not surprising if in the hadith the mother is mentioned 3x and then the father. 2) Management of children's education carried out by parents, especially mothers, there are three things including: learning management which includes learning at school, home or tutoring, religious activity management includes the practice of religious activities carried out daily to strengthen the theory obtained, play management where it is important for children to learn socially and learn related to the environment so that children should not be prohibited from playing outside as long as they remain under supervision either remotely or closely.